Implementation of Text Message Security for Ordering Weapons with the RC4 Algorithm Method - Wikik Andhitias Sutrisno; Rudy A.G. Gultom; Yudistira Dwi Wardana (Journal on Education, 2024)
The development of communication technology is currently growing rapidly so that it can help all activities. including ordering weapons by the military. this can cause problems when ordering weapons is known by irresponsible people. this can be minimized using information protection techniques that can be kept confidential from irresponsible people. One of the techniques that can be used is cryptographic techniques on text messages. Cryptography is a technique for writing secret messages so that people don't easily understand the messages inside. in this study using the RC4 algorithm. The RC4 algorithm is one of the methods used to create secret messages with message encryption and decryption techniques. This study aims to design cryptographic applications in securing text messages.